Use of Vacuum to Increase the Effectiveness of X-Ray Tube Maintenance - Alya Izzaty Bika; Meilia Safitri; Erika Loniza; Bagus Roni Yusuf; Djoko Sukwono (Journal of Fuzzy Systems and Control, 2023)
Each device requires redundancy, including the X-ray machine. In an X-ray machine, there is an important component as the location for the creation of X-rays, namely the X-ray tube. This tube needs routine maintenance to increase the tube's lifetime. In addition, maintenance that was originally done manually, with this device can be done automatically and more quickly. In addition, maintenance that was originally done manually can be done automatically and faster with this device. X-ray tube oil vacuum is used as an effective solution for the maintenance of an X-ray tube machine that lasts for days. This device comes with easy use, equipped with two buttons and a display. This device can increase the productivity of both the device and the technician itself. The application of the use of X-ray tube oil vacuum is intended for hospitals and health facilities that have active X-ray machines. This device has been able to be built. Based on the results, it has a 2.5% error for the measurement at minimum and maximum pressure and a 3% error at -15 KPa pressure. The volume of the X-ray tube fully filled is always the same for each measurement. It can be concluded that this device can be effective in time because it only takes minutes to fill the X-ray tube up to full. Still, many parts can be improved and developed, such as the size and the weight.